E-130 Incidence and outcomes of large vessel occlusion stroke after cardiac surgery at a major academic medical center. (22nd July 2019) - Wilkinson, D; Koduri, S; Burke, J; Gemmete, J; Chaudhary, N; Patel, H; Pandey, A
Abstract : Background and purpose: Stroke is one of the most feared complications of cardiac surgery. Modern stent-retrieval techniques provide effective treatment for large vessel occlusive strokes. The purpose of this study was to 1) report the incidence of large vessel occlusive stroke after cardiac surgery at a large academic center, and 2) describe outcomes after postoperative large vessel occlusive strokes (LVOs) associated with cardiac surgery. Methods: All patients experiencing stroke within 30 days after undergoing cardiac surgery via an open or endovascular approach at a major academic medical center in 2015–2017 were reviewed. LVOs were identified through review of imaging and medical records and their characteristics and clinical courses were examined. Results: Over the study period, 4, 209 cardiac surgeries, including endovascular procedures, were performed. Of 111 patients classified as having stroke, 8 had LVO. Two of the three patients who received mechanical thrombectomy returned to independent living, compared to only 1 of the 5 patients who did not undergo thrombectomy. In the 2 weeks following cardiac surgery, the rate of LVO was estimated at 200x that of the general population. Conclusion: Of patients undergoing cardiac surgery at an academic medical center, 0.2% (95% CI 0.1–0.4%) had LVO within 30 days. Cardiac surgery patients and their caregivers should be counseled about the warning signs of stroke, the importance of timely intervention, and how to seek emergency care in the postoperative period. Disclosures: D. Wilkinson: None. S. Koduri: None. J. Burke: None. J. Gemmete: None. N. Chaudhary: None. H. Patel: None. A. Pandey: None.